THE MAGMATIC SULPHIDE CU-NI DEPOSITS AND THEIR EARTH DYNAMICS SETTING IN NORTH OROGENIC BELT OF CHINA: A CASE STUDY OF HONGQILING DEPOSITS - Xi A.; Gu L.; Zheng Y.; Li X. (My University, 2006)
Large amount of geological research indicates that there are series Cu-Ni sulphide deposits in south central Jilin Province, eastern portion of the Xing'an-Mongolian Orogenic belt, North China. Hongqiling Cu-Ni sulphide deposit represents the type related to ultramafic-mafic magmatic processes in the Early Triassic period. The parent rocks for the deposits are consist mainly of mafic-ultramafic complex of gabbro-websterite-olivine websterite - Iherzolite and dykes of orthopyroxenite, what constituting four types ore with sparse disseminations and sideronitic texture, dense disseminations texture, patched structure and massive structure. The silicate minerals assemblages as olivine + othopyroxenes + clinopyroxenes + amphiboles + plagioclases± phlogopite, similar to the calc-alkaline series rocks. Petrological works has proved that mafic-ultramafic rocks are enriched in LREE and Rb, Ba and depleted in Nb Ti conformed with the subduction related tholeiite, maybe presented a result that parental magma was derived from mantle source and contaminated with the Crust. Isotopic dating confirms that the intrusions were emplaced at about 250Ma, the Early Triassic, being similar to the time of the syn-orogenic granite widely found in North China. It implies that the ore-bearing intrusions are products of magmatic activities under a transition period from extrusion to extension system and was related to the colliding orogeny between the north China plate and the Siberia Plade.
Keywords: CU-NI SULPHIDE DEPOSIT; HONGQILING DEPOSIT; NORTH OROGENIC BELT OF CHINA; THE EARTH DYNAMICS SETTING; Мезозой::Триасовая; Mesozoic::Triassic